Profile of women receiving first-trimester safe abortion service at Paropakar Maternity and Women’s Hospital - Shrestha, Shanti; Dangal, Ganesh; Ghimire, Sadikshya (Journal of Chitwan Medical College, 2021)
Background: Abortion is a common medical procedure done in a day to day basis in every country and is a major component of public health. Legally and safely performed abortions are amongst the least complicated medical procedures. There exists a demographic variation in availability, accessibility and affordability of safe abortion services in Nepal also. The aim of the study was to assess the demographic and clinical profile of women opting for first-trimester abortion. This study highlights the indications and rate of the method used for abortion. Methods: It was a retrospective study where data were collected from charts available at the comprehensive abortion care center at the Paropakar Maternity and Women’s Hospital. The data from Baisakh to Asoj of 2076 B.S was collected and calculations were done manually. Results: Higher proportion of women receiving first-trimester abortion fell under the age of 26-30 years (30.17%). Most women were literate (86.03%) and married (85.71%). A history of previous abortion was absent in majority (72.39%) and 14.28% had never been pregnant before. The most common indication for abortion was non-use of family planning services (43.82%). The rate of medical abortion was higher (58.10%) than surgical method of abortion (41.89%). Conclusions: Women’s age, literacy, contraceptive use, previous pregnancy status were the determinants of unintended pregnancy. There existed both demographic and clinical variations in between women receiving abortion services.